Effect of different sources of dietary zinc on sperm quality and oxidative parameters - Mousavi Esfiokhi, Seyed Hamid; Norouzian, Mohammad Ali; Najafi, Abouzar (Frontiers in Veterinary Science, 2023)
Zinc has a critical physiological role in sperm function. The purpose of this study was to investigate the effect of different sources of zinc on sperm quality. For this purpose, 18 Zandi lambs with an average weight of 32 ± 1.2 kg were subjected to three treatments in a completely randomized design. Experimental treatments include 1) control treatment of basal diet without zinc supplementation, 2) basal diet with 40 mg / kg of zinc supplementation from zinc sulfate source and 3) basal diet with 40 mg / kg of zinc supplementation with organic source. At the end of feeding period, lambs were slaughtered. To determine the effect of experimental treatments on sperm quality, the testes were transferred to the laboratory. After that, epididymal spermatozoa were evaluated for sperm motility parameters, abnormal morphology, viability, membrane functionality, malondialdehyde (MDA) and antioxidant activity (glutathione peroxidase (GPx), superoxide dismutase (SOD), total antioxidant capacity (TAC)), sperm concentration and testosterone level. Zinc sulfate administration decreased MDA levels compared to other treatments and increased GPx and TAC activity compared to the control (P <0.05), although SOD activity was not affected by any supplementation. Also, the use of zinc sulfate supplementation increased the percentage of total and progressive motility compared to the control group (P <0.05). Membrane integrity and sperm viability were also affected by zinc sulfate supplementation (P <0.05). Therefore, the results of this study showed that the use of zinc sulfate, can improve sperm motility and survival indices and its antioxidant capacity.